Traumatic injuries in patients with diabetes mellitus - Ayman El-Menyar; Ahammed Mekkodathil; Hassan Al-Thani (Journal of Emergencies, Trauma and Shock, 2016)
Diabetes mellitus (DM) is associated with increased in-hospital morbidity and mortality in patients sustained traumatic injuries. Identification of risk factors of traumatic injuries that lead to hospital admissions and death in DM patients is crucial to set effective preventive strategies. We aimed to conduct a traditional narrative literature review to describe the role of hypoglycemia as a risk factor of driving and fall-related traumatic injuries. DM poses significant burden as a risk factor and predictor of worse outcomes in traumatic injuries. Although there is no consensus on the impact and clear hazards of hyperglycemia in comparison to the hypoglycemia, both extremes of DM need to be carefully addressed and taken into consideration for proper management. Moreover, physicians, patients, and concerned authorities should be aware of all these potential hazards to share and establish the right management plans.